Crystalluria in various groups of sportsmen - Cox, Tracy-Ann (Department of Chemistry, 2017)
This thesis examines various groups of athletes to assess whether they are at risk with regard to kidney stone formation. Particle size distribution analysis (Coulter counter), ultra-structural analyses (SEM) and urine analysis were conducted. The background to various factors relating to stone formation is discussed as well as the general theory behind the techniques employed. The methods utilized and data obtained are described. Particle size distribution analysis and scanning electron· micrographs suggest that marathon runners and cyclists may be at risk with respect to stone formation. Dehydration and urinary tract trauma are thought to occur in the former whereas dehydration only is operative in the latter. Results obtained from Na/Ca ratio analyses are found to correspond with the particle size analyses thereby suggesting that this ratio may have potential as a useful index of stone-forming risk. The enormous spread of values amongst each class of athlete shows, however, that physical exertion is not the sole factor affecting the Na/Ca ratio.